Distinct functionality of dishevelled isoforms on Ca2+/calmodulin-dependent protein kinase 2 (CamKII) in Xenopus gastrulation. - Gentzel, Marc; Schille, Carolin; Rauschenberger, Verena; Schambony, Alexandra (Molecular Biology of the Cell, 2015)
Wnt ligands trigger the activation of a variety of β-catenin-dependent and β-catenin-independent intracellular signaling cascades. Despite the variations in intracellular signaling, Wnt pathways share the effector proteins frizzled, dishevelled, and β-arrestin. It is unclear how the specific activation of individual branches and the integration of multiple signals are achieved. We hypothesized that the composition of dishevelled-β-arrestin protein complexes contributes to signal specificity and identified CamKII as an interaction partner of the dishevelled-β-arrestin protein complex by quantitative functional proteomics. Specifically, we found that CamKII isoforms interact differentially with the three vertebrate dishevelled proteins. Dvl1 is required for the activation of CamKII and PKC in the Wnt/Ca(2+) pathway. However, CamKII interacts with Dvl2 but not with Dvl1, and Dvl2 is necessary to mediate CamKII function downstream of Dvl1 in convergent extension movements in Xenopus gastrulation. Our findings indicate that the different Dvl proteins and the composition of dishevelled-β-arrestin protein complexes contribute to the specific activation of individual branches of Wnt signaling.

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

Erratum to: Gap junction protein Connexin-43 is a direct transcriptional regulator of N-cadherin in vivo (Nature Communications, (2018), 9, 1, (3846), 10.1038/s41467-018-06368-x) - Kotini, Maria; Barriga, Elias H.; Leslie, Jonathan; Gentzel, Marc; Rauschenberger, Verena; Schambony, Alexandra; Mayor, Roberto (Nature Communications, 2018)
Correction to: Nature Communications (2018); https://doi.org/10.1038/s41467-018-06368-x, published online 21 September 2018 The original version of this Article contained an error in the spelling of the author Alexandra Schambony, which was incorrectly given as Alexandra Schambon. This has now been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2022-08-05

Interferometric scattering microscopy reveals microsecond nanoscopic protein motion on a live cell membrane - Taylor, Richard W.; Mahmoodabadi, Reza Gholami; Rauschenberger, Verena; Gießl, Andreas; Schambony, Alexandra; Sandoghdar, Vahid (Nature Photonics, 2019)
Many of the biological functions of a cell are dictated by the intricate motion of proteins within its membrane over a spatial range of nanometres to tens of micrometres and time intervals of microseconds to minutes. This rich parameter space is not accessible by fluorescence microscopy, but it is within reach of interferometric scattering (iSCAT) particle tracking. However, as iSCAT is sensitive even to single unlabelled proteins, it is often accompanied by a large speckle-like background, which poses a substantial challenge for its application to cellular imaging. Here, we employ a new image processing approach to overcome this difficulty and demonstrate tracking of transmembrane epidermal growth factor receptors with nanometre precision in all three dimensions at up to microsecond speeds and for durations of tens of minutes. We provide examples of nanoscale motion and confinement in ubiquitous processes such as diffusion in the plasma membrane, transport on filopodia and rotational motion during endocytosis.
CRIS-Team Scopus Importer:2019-05-02

ROR-Family Receptor Tyrosine Kinases. - Stricker, Sigmar; Rauschenberger, Verena; Schambony, Alexandra (Current Topics in Developmental Biology, 2017)
ROR-family receptor tyrosine kinases form a small subfamily of receptor tyrosine kinases (RTKs), characterized by a conserved, unique domain architecture. ROR RTKs are evolutionary conserved throughout the animal kingdom and act as alternative receptors and coreceptors of WNT ligands. The intracellular signaling cascades activated downstream of ROR receptors are diverse, including but not limited to ROR-Frizzled-mediated activation of planar cell polarity signaling, RTK-like signaling, and antagonistic regulation of WNT/β-Catenin signaling. In line with their diverse repertoire of signaling functions, ROR receptors are involved in the regulation of multiple processes in embryonic development such as development of the axial and paraxial mesoderm, the nervous system and the neural crest, the axial and appendicular skeleton, and the kidney. In humans, mutations in the ROR2 gene cause two distinct developmental syndromes, recessive Robinow syndrome (RRS; MIM 268310) and dominant brachydactyly type B1 (BDB1; MIM 113000). In Robinow syndrome patients and animal models, the development of multiple organs is affected, whereas BDB1 results only in shortening of the distal phalanges of fingers and toes, reflecting the diversity of functions and signaling activities of ROR-family RTKs. In this chapter, we give an overview on ROR receptor structure and function. We discuss their signaling functions and role in vertebrate embryonic development with a focus on those developmental processes that are affected by mutations in the ROR2 gene in human patients.

The phosphatase Pgam5 antagonizes Wnt/β-catenin signaling in embryonic anterior-posterior axis patterning - Rauschenberger, Verena; Bernkopf, Dominic; Krenn, Sabrina; Jalal, Kowcee; Heller, Jens; Behrens, Jürgen; Gentzel, Marc; Schambony, Alexandra (Development, 2017)
Keywords: Anteriorposterior patterning; Dvl2; Pgam5; Phosphatase; Wnt; Xenopus